Challenges in Mongolia's building cooling systems sector: A survey of industry professionals (Journal of Applied Science and Engineering A, 2025)
Driven by global warming and rapid urbanization, summer air temperatures in Mongolia are rising and cooling demand in commercial and public buildings is growing steadily. Research systematically examining the challenges faced across the design, installation, and operation stages of cooling systems remains limited, however, and no independent calculation platform adapted to Mongolia's climatic conditions has yet been established.This study characterizes the current state of the sector, identifies the challenges faced by industry professionals, and assesses the need for an independent calculation platform to improve the quality of cooling system design and operation. Using purposive sampling, 40 heating, ventilation, and air-conditioning (HVAC) professionals were surveyed: 18 design engineers, 14 installation engineers, and 8 operation engineers and technicians. Data were collected in March 2026 via a conditional, branched questionnaire hosted on the coolcalc.mn online platform.Results show that 88.9% of design engineers rely on an experience-based rule-of-thumb (W/m²) sizing approach, while only 16.7% apply the ASHRAE load-calculation procedures, and 50.0% calculate neither capital expenditure (CAPEX) nor operating expenditure (OPEX). Among installation engineers, 92.9% reported that space for equipment placement is not allocated in the design, and 92.9% highlighted a shortage of qualified operations personnel. Only 25.0% of operation engineers reported that their systems are fully operational; 62.5% of this group identified insufficient operational knowledge as the sector's most critical issue. Across all respondents, 90.0% expressed interest in a brand-neutral calculation platform aligned with international standards.The findings indicate a need for a locally adapted, standards-compliant calculation tool, alongside reforms in professional training and regulatory codes, to improve building energy efficiency and support Mongolia's sustainable urban development goals.